2007
DOI: 10.3354/meps07008
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixation by symbiotic cyanobacteria provides a source of nitrogen for the scleractinian coral Montastraea cavernosa

Abstract: Colonies of the Caribbean coral Montastraea cavernosa (Linnaeus) that harbor endosymbiotic cyanobacteria can fix nitrogen, whereas conspecifics without these symbionts cannot. The pattern of nitrogen fixation is diurnal and maximum rates occur in the early morning and evening. An analysis of δ 15 N stable isotope data showed that the zooxanthellae, but not the animal tissue, from colonies with cyanobacteria preferentially use the products derived from nitrogen fixation, and that these zooxanthellae also have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
249
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(266 citation statements)
references
References 39 publications
15
249
2
Order By: Relevance
“…Lesser et al (2004) proposed phycoerythrin and the nifH gene as indicators for the presence of diazotrophic cyanobacteria in the epithelial cells of Montastrea cavernosa. While this coral was subsequently reported to be actively fixing N 2 (Lesser et al, 2007), Oswald et al (2007) demonstrated that phycoerythrin as analyzed in the previous study can give falsepositive signals leading to an overestimation of the density of cyanobacteria in the tissue. By this time, the advent of new molecular biology techniques started to allow more detailed descriptions of the identity of coral-associated diazotrophs, but much work needed (and in still needs) to be done to establish whether these associated diazotrophs were coral species-or site-specific, whether they were permanent residents of the coral holobiont transmitted vertically through generations, or acquired horizontally when needed to confront nitrogen scarcity conditions.…”
Section: Diversity Of Diazotrophs In Tropical Coralsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesser et al (2004) proposed phycoerythrin and the nifH gene as indicators for the presence of diazotrophic cyanobacteria in the epithelial cells of Montastrea cavernosa. While this coral was subsequently reported to be actively fixing N 2 (Lesser et al, 2007), Oswald et al (2007) demonstrated that phycoerythrin as analyzed in the previous study can give falsepositive signals leading to an overestimation of the density of cyanobacteria in the tissue. By this time, the advent of new molecular biology techniques started to allow more detailed descriptions of the identity of coral-associated diazotrophs, but much work needed (and in still needs) to be done to establish whether these associated diazotrophs were coral species-or site-specific, whether they were permanent residents of the coral holobiont transmitted vertically through generations, or acquired horizontally when needed to confront nitrogen scarcity conditions.…”
Section: Diversity Of Diazotrophs In Tropical Coralsmentioning
confidence: 99%
“…Another hot spot of N 2 fixation in reefs is represented by microbial mats (where N 2 fixation can be as high as 3.2 nmol N cm −2 h −1 or a mean of 1.66 nmol N cm −2 h −1 ) with beach-rock showing the highest rates (Charpy-Roubaud and Larkum, 2005). Compared to the above substrates, N 2 fixation is much lower when diazotrophs are associated to sponges (Shashar et al, 1994;Rix et al, 2015) and soft coral species (0.001 to 0.205 nmol C 2 H 4 cm −2 h −1 or maximum of 0.07 nmol N cm −2 h −1 ; Bednarz et al, 2015a), but can increase in the presence of scleractinian coral species up to 8.7 nmol C 2 H 4 cm −2 h −1 (Davey et al, 2008;or 2.8 nmol N cm −2 h −1 ; Shashar et al, 1994;Lesser et al, 2007), as well as in turf algae (Haan et al, 2014;Rix et al, 2015). The dominance of BOX 1 | Methodological considerations for N 2 fixation measurements N 2 fixation rates can be assessed through different methods, mainly the acetylene (C 2 H 2 ) reduction assay (ARA; Capone, 1993) and the 15 N 2 enrichment technique (Montoya et al, 1996).…”
Section: N 2 Fixation In Coral Reef Ecosystems Description Of N 2 Fixmentioning
confidence: 99%
“…Consequently, symbioses with nitrogen-fixing organisms (diazotrophs) that convert the abundant gas dinitrogen (N 2 ) into more usable forms like ammonium (NH 4 + ) provide important supplemental sources of nitrogen. Although evidence is mounting that nitrogen-fixing bacteria are associated with corals (Shashar et al, 1994;Lesser et al, 2004Lesser et al, , 2007Kvennefors and Roff 2009;Olson et al, 2009;Kimes et al, 2010;Lema et al, 2012;Santos et al, 2014;Lema et al, 2014a,b), to date the location of nitrogen-fixing bacteria within coral tissues and evidence that fixed nitrogen is available to corals or their endosymbiotic algae, Symbiodinium, remains elusive. Techniques such as nanoscale secondary ion mass spectrometry (NanoSIMS), which is able to map enriched stable isotope (for example, 13 C, 15 N and so on) tracers at the cellular scale, provides a powerful tool for co-locating diazotrophs within coral tissues.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the growth and abundance of zooxanthellae is limited by the availability of nitrogen (Falkowski et al, 1993). In nitrogen-limited coral systems, the abundance of zooxanthellae may depend on the activity of diazotrophic bacteria (Lesser et al, 2007;Olson et al, 2009;Lema et al, 2012).…”
Section: Introductionmentioning
confidence: 99%